The politics of nationalism and ethnicity - Kellas, James G. (St Martin's Press, 1998)
Nationalism and ethnicity have always been key elements in state-building and in the break-up of states, and never more so than in the world today. While there are many partial theories, there is no coherent general theory which adequately explains nationalism's political significance and salience. In this comprehensively revised and updated new edition, James Kellas reviews and assesses the main theoretical approaches to the study of nationalism that have been developed within a wide range of disciplines. He introduces a range of international case studies to explain the power of nationalism and ethnicity in politics, to identify the circumstances in which they flourish, and to evaluate various strategies of accommodation which have been developed to contain ethnic conflict.